Implementing Differentiated Instruction with AI in Indonesian EFL Education Context - Muslimin, Afif Ikhwanul; Harintama, Fitrana (ELITE JOURNAL, 2025)
This article delves into the integration of artificial intelligence (AI) tools to implement differentiated instruction in the Indonesian EFL education context. By leveraging AI platforms such as Quizzez, Readtheory, and HiNative, educators can personalize learning experiences, provide immediate feedback, and cater to diverse student interests and proficiency levels. The case studies presented highlight the benefits of using AI for enhancing reading comprehension, vocabulary expansion, and presentation skills in EFL classrooms. Through strategic planning and utilization of AI-powered tools, educators can effectively address the unique learning needs of students, promote engagement, and foster a conducive learning environment for language acquisition and skill development.